The relationship between supervision contextual factors and supervision outcomes - Ghazali, Nor Mazlina; Wan Jaafar, Wan Marzuki; Ahmad Tarmizi, Rohani; Mohd Noah, Sidek (Human Resource Management Academic Research Society, 2018)
The purpose of this study was to investigate the influence of the supervisory relationship and contextual supervision factors on supervision outcomes among trainee counsellors. There were 120 trainee counsellor respondents and 18 supervisors from four universities UM, UUM, UMT and UMS. The respondents were selected using the stratified random sampling technique. This study utilized the correlational research design. His research revealed there was no significant correlations between supervision contextual factors (supervisees’ and supervisors’ counselling orientation and supervisees’ cultural knowledge and awareness) and supervision outcomes. There were several recommendations outlined by the study which included, (i) the supervision contextual factors (cultural knowledge and awareness) should be examined from the supervisors’ perspective, (ii) future researchers should personally give explanations to the respondents when conducting the question and answer sessions and (iii) future researchers could also expand this investigation by examining the differences between supervision interaction of the supervisors and the supervisees.